A micro-level view on knowledge co-creation through university-industry collaboration in a multi-national corporation. Issue 5 (6th May 2020) - Jones, Shannon Elizabeth; Coates, Nigel
Abstract : Purpose: Technology transfer (TT) in industry to university collaboration (UIC) literature focuses primarily on a macro view within an SME environment. While these discussions are important to establish the significance of encouraging UIC's as the value is important to both parties, there is a need for further research at a micro level to help understand key approaches to ensuring the success of the TT. By looking at how value created from TT for a multi-national corporation (MNC) with a project based within a single subsidiary, this research effectively looks at the issue from both a SME level (the subsidiary independently) and a MNC level. Design/methodology/approach: The research uses a longitudinal knowledge transfer partnership and action research to form a case study of Parker Hannifin's Gas Separation and Filtration Europe, Middle East and Africa (GSFE) division. Findings: The research highlights the key areas to focus on in ensuring a successful TT within an UIC such as: once identifying the gap that a UIC is filling in the company, identifying internal barriers before the project starts; education of why change is necessary and then using knowledge experts to educate on the new processes being introduced and finally; incorporation of a full range of personnel, not just those directly involved in the day-to-day of the UIC. Research limitations/implications: As a case study, further research is required to make the results more generalisable. One way to do this would be to evaluate previous successful and unsuccessful UIC's and determine if the success criteria identified were present in these programmes. Practical implications: There are three critical points that can be taken away from this research and applied to any company looking to use UIC for TT and value co-creation. Education, external knowledge experts and business wide inclusion were highlighted in the findings as being potentially critical turning points and need to be addressed for successful TT. Social implications: Successful UIC's further encourage investment in such programmes which has greater societal benefits. Not only can we see greater leaps in industry through better, more specific knowledge being transferred from the university, the industry knowledge fed into universities helps to guide research and teachings. Originality/value: The micro level view created by action research based from the industry partner perspective adds another level of importance as the "how" for overcoming barriers is clearly addressed. Furthermore, the research looks at how a multi-national corporation can have value added through UIC's within subsidiaries which often is not addressed in the literature.